2021
DOI: 10.3389/fimmu.2021.708523
|View full text |Cite
|
Sign up to set email alerts
|

Declining Levels of Neutralizing Antibodies Against SARS-CoV-2 in Convalescent COVID-19 Patients One Year Post Symptom Onset

Abstract: Major advances have been made in understanding the dynamics of humoral immunity briefly after the acute coronavirus disease 2019 (COVID-19). However, knowledge concerning long-term kinetics of antibody responses in convalescent patients is limited. During a one-year period post symptom onset, we longitudinally collected 162 samples from 76 patients and quantified IgM and IgG antibodies recognizing the nucleocapsid (N) protein or the receptor binding domain (RBD) of the spike protein (S). After one year, approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 32 publications
9
58
0
Order By: Relevance
“…Our results reveal that in most cases, SARS-CoV-2 S-specific IgG levels remained stable over time and SARS-CoV-2 NCP-specific IgG levels decreased to a stable level within 6–12 months after symptom onset, while their range continuously diminished. Recent studies show that SARS-CoV-2-specific antibody levels after an infection were detectable in the majority of donors over a period of up to 1 year, even though the rate of recession varied ( 9 , 11 , 12 , 26 , 27 ). This supports our findings from the long-term analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results reveal that in most cases, SARS-CoV-2 S-specific IgG levels remained stable over time and SARS-CoV-2 NCP-specific IgG levels decreased to a stable level within 6–12 months after symptom onset, while their range continuously diminished. Recent studies show that SARS-CoV-2-specific antibody levels after an infection were detectable in the majority of donors over a period of up to 1 year, even though the rate of recession varied ( 9 , 11 , 12 , 26 , 27 ). This supports our findings from the long-term analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our findings from the long-term analysis. Some studies show only similar progressions for anti-S and anti-N antibody levels over time ( 26 , 27 ) whereas a study by Wang and colleagues assessed anti-RBD as well as anti-N antibodies and found stable levels of anti-RBD IgG compared to a reduction of anti-N IgG levels ( 11 ). This has also been observed in our results which suggest that the descent of anti-N IgG levels is more pronounced in comparison to the course of anti-S IgG.…”
Section: Discussionmentioning
confidence: 99%
“…In convalescent SARS-CoV-2 infected individuals, evidence showed that nAbs can sustain for over a year and exhibited a longer duration of detectable antibody with severe disease patients; however, the nAbs responses were not affected by different age groups [ 17 ]. This may be due to individuals infected with SARS-CoV-2 with older age having higher chances to develop severe diseases presentation, thus generating higher titer of nAbs [ 17 , 18 , 19 ]. We did not observe statistical differences of anti-N or anti-S existence status in HCWs with and without ARDS in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…84 In addition to this, there are reports regarding the kinetics of natural immunity in patients who had COVID-19. In a study, 85 the humoral response was evaluated in a total of 76 patients (IgM and IgG antibodies that recognized the nucleocapsid protein or the RBD of the S-protein). In these patients 1 year after infection, approximately 90% of recovered patients still had detectable SARS-CoV-2-specific IgG antibodies recognizing N and RBD-S.…”
Section: Ade As a Possible Threat To Vaccine Efficacymentioning
confidence: 99%